High deductible health plans and spending among families with a substance use disorder. (1st December 2022) - Meiselbach, Mark K.; Kennedy-Hendricks, Alene; Schilling, Cameron; Busch, Alisa B.; Huskamp, Haiden A.; Stuart, Elizabeth A.; Hollander, Mara A.G.; Barry, Colleen L.; Eisenberg, Matthew D.
Abstract: Background: The United States faces an ongoing drug crisis, worsened by the undertreatment of substance use disorders (SUDs). Family enrollment in high deductible health plans (HDHPs) and the resulting increased cost exposure could exacerbate the undertreatment of SUD. This study characterized the distribution of health care spending within families where a member has a SUD and estimated the association between HDHPs and family health care spending. Methods: Using commercial claims and enrollment data from OptumLabs (2007–2017), we identified a treatment group of enrollees whose employers began offering an HDHP and comparison group whose employers never offered an HDHP. We used a difference-in-differences analysis that compared health care spending in families at firms that did vs. did not offer an HDHP before and after the HDHP offer. All models were adjusted for employer and year fixed effects, as well as family demographics, size, and chronic conditions. Results: Our sample was comprised of 317, 353 family-years. Family members with a SUD, on average, contributed an outsized proportion of total family health care expenditures (56.9% in a family of three). Offering a family HDHP was associated with a 6.1% reduction (95% confidence interval [CI]: 9.7–2.6%) in the probability of families having any SUD-related expenditures. The HDHP offer was associated with a 1546 reduction in family total expenditures and a 1185 reduction for the individual with SUD (95% CI: −2272 to −821 and −1845 to −525, respectively). Conclusions: The increased prevalence of family enrollment in HDHPs may further the existing issue of undertreatment of SUDs. Highlights: Family members with a substance use disorder had plurality of family's health expenditures. High deductibles associated with lower probability of treatment for substance use disorders. High deductibles associated with lower total family health expenditures.